Effect of the Hypoxia Inducible Factor on Sorafenib Resistance of Hepatocellular Carcinoma - Zeng, Zhi; Lu, Qiliang; Liu, Yang; Zhao, Junjun; Zhang, Qian; Hu, Linjun; Shi, Zhan; Tu, Yifeng; Xiao, Zunqiang; Xu, Qiuran; Huang, Dongsheng (Frontiers in Oncology, 2021)
Sorafenib suppresses tumor angiogenesis, cell proliferation, and promotes apoptosis, as a multi-target tyrosine kinase inhibitor and first-line drug in advanced hepatocellular carcinoma (HCC), it is also one of the few chemotherapy options for patients with advanced HCC. Sorafenib can effectively prolong the median survival of patients with advanced HCC, however, because of drug resistance, patients can benefit limitedly. Multiple complex mechanisms are involved in HCC sorafenib resistance. Clinical data shows that HIFs expression disorders in HCC patients are powerful indicators of poor prognosis. Currently, the combination of sorafenib therapy with HIFs-targeted therapy or HIFs inhibitors has been shown to be a promising approach to overcome HCC sorafenib resistance in vitro and vivo. Here we briefly introduce the molecular mechanism of sorafenib resistance in HCC and the relevance between the hypoxia microenvironment and sorafenib resistance.